Answer: A Step-by-step explanation: Given 4 – t = 3(t – 1) – 5 ← distribute and simplify right side 4 – t = 3t – 3 – 5 4 – t = 3t – 8 ( subtract 4 from both sides ) – t = 3t – 12 ( subtract 3t from both sides ) – 4t = – 12 ( divide both sides by – 4 ) t = 3 → A Log in to Reply

Answer:A

Step-by-step explanation:Given

4 – t = 3(t – 1) – 5 ← distribute and simplify right side

4 – t = 3t – 3 – 5

4 – t = 3t – 8 ( subtract 4 from both sides )

– t = 3t – 12 ( subtract 3t from both sides )

– 4t = – 12 ( divide both sides by – 4 )

t = 3 → A